Georg Joseph Vogler (1749-1814) - Bittheuser (engraver):::Creator::::::::::::; Hauber, Joseph, 1766-1834 (artist):::Contributor:::::::::::: (Kunstverlag; Germany; Schweinfurt, 2020)
Portrait engraving of Abbé G. J. Vogler (1749-1814) composing at his desk with quill pen in hand, based on a painting by Joseph Hauber from 1808.